The joint impact of job complexity, autonomy, and personality differences on employee job stress - Li, Junchao; Burch, Tyler (My University, 2013)
This paper extends our understanding on how job complexity influences employees’ job stress. Prior research on job complexity suffers from inconsistent conceptualizations and vagueness in its theoretical meaning. Operationalizing job complexity from the perspective of knowledge and skills needed, this study examines the relationship between job complexity and job stress with two sets of longitudinal data. We find that job complexity exerts a positive, curvilinear effect on employee job stress. As job complexity increases, the marginal increment of job stress triggered by job complexity becomes larger. Also, based on job-demand-control theory and person-situation interaction, we propose that job autonomy and employees’ personality (openness to experience and emotional stability) jointly moderate the relationship between job complexity and employees’ job stress. Specifically, the results of the three-way interactions reveal that (1) for employees with high emotional stability/openness to experience, job autonomy manages to mitigate the positive relationship between job complexity and job stress, whereas (2) for employees with low emotional stability/openness to experience, job autonomy does not help to reduce the undesirable effect of job complexity on job stress. Theoretical and practical implications are discussed.
Keywords: Employment -- Occupations and careers; Human Capital -- Labour; Labour market; Human Capital; Employment; Occupations and careers; Labour; Employment and unemployment